PHONETIC AND PEDAGOGICAL BARRIERS IN ARABIC READING AMONG NON-NATIVE SECONDARY STUDENTS IN PERLIS: A DESCRIPTIVE-ANALYTICAL STUDY - Noorzamri, Nurul Husna; Zabidin, Mohd Azizul Rahman; Abd Elgadir, Ibrahim Babikir Elhag (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Reading is a fundamental phonetic skill and plays a vital role in the teaching and learning of languages. Accurate pronunciation of letters, words, and sentences is key to conveying intended meaning. However, non-native Arabic learners often face challenges in this area, reflected in frequent pronunciation errors during reading. This study aims to identify the primary difficulties faced by secondary school students in Perlis in mastering Arabic reading skills. Employing a descriptive-analytical method, the research explores the types and stages of reading, highlighting their impact on skill development. Data were collected using a questionnaire distributed among students and analyzed to determine the most significant barriers to effective reading. The findings indicate that students struggle particularly with pronouncing certain Arabic sounds due to phonetic differences between Arabic and their native languages. These difficulties hinder their comprehension and reading fluency. This study contributes to the field of Arabic language education for non-native speakers by pinpointing key obstacles and proposing targeted pedagogical solutions.